A Virus among the functioning of the new high school - Casagrande, Ana Lara [UNESP] (Associacao Pro-Ensino Superior em Novo Hamburgo, 2021)
It explores the impact of the Covid-19 pandemic and the changes instituted by Law n° 13,415, of February 16, 2017, in High School, through exploratory research, which involves bibliographic and documentary surveys, seeking to provide an overview , of an approximate type on the facts presented. The uncertainties brought to the final stage of Basic Education, which is undergoing structural changes, compose a scenario of great insecurity for heterogeneous, plural youth, and immersed in an unequal social and economic system. New forms of exclusion promoted from within the educational system are noted, with the pandemic and reconfiguration of high school (although the strategies are proclaimed are directed, among others, to the stimulus to youth protagonism), whose consequences are a negatively improved portrait from the previous context. It will be essential to debate broadly the changes aimed at high school and the consequences of remote education for a large contingent of young people, after this era of the unforeseen, in order to further minimize the chaos for their futures.
Um virus em meio ao aparelhamento do novo ensino medio
Keywords: High school; Pandemic; Restructuring